“A CLINICAL STUDY TO EVALUATE THE ASSOCIATION OF HBA1C TITRES IN TYPE 2 DIABETES MELLITUS AND SEVERITY OF SENSORINEURAL HEARING LOSS” - Dr Neha Kishnani; Dr Satyam; Prof. Dr Vikram Singh Rathore (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Type 2 Diabetes Mellitus (T2DM) is a chronic metabolic disorder associated with several complications, including the underrecognized impact on auditory function. Sensorineural hearing loss (SNHL), particularly at higher frequencies, may be influenced by poor glycaemic control, as reflected by elevated HbA1c levels. Objective: To evaluate the association between HbA1c titres and the severity of SNHL in patients with T2DM. Methods: This cross-sectional observational study was conducted over 12 months at a tertiary care hospital in India, enrolling 70 T2DM patients aged 30–75 years. Patients underwent HbA1c testing and Pure Tone Audiometry (PTA). SNHL severity was categorized using WHO grades, and associations with HbA1c were statistically analyzed using chi-square, Pearson correlation, and ROC analysis. Results: The majority of participants were aged 60–69 years (34%), with moderate or severe SNHL. Poor glycaemic control was common, with 37% of participants having sub-optimal HbA1c levels (7–8.9%) and 37% with poor control (≥9%). The severity of SNHL showed a clear association with glycaemic status: 33% of those with HbA1c < 7%, 54% with HbA1c 7–8.9%, and 100% with HbA1c ≥ 9% had moderate or severe SNHL (p < 0.001). ROC analysis identified an HbA1c cut-off of 8.7% for predicting moderate SNHL, with good diagnostic accuracy (AUC 0.79, sensitivity 77%, specificity 72%). Conclusion: Poor glycaemic control is significantly associated with increased SNHL severity in T2DM patients. Audiological screening should be integrated into routine diabetic care to detect early hearing impairment.